Klasifikasi Jenis Buah Pisang Menggunakan Algoritma Convolutional Neural Network - Fadila Huda; M. Pajar Kharisma Putra (PT. Tech Cart Press, 2023)
This research aims to address challenges in classifying types of banana using the Convolutional Neural Network (CNN) algorithm. The research background reflects the need for an automatic classification system to enhance the efficiency of banana farmers, considering that the manual methods still widely used have weaknesses in consistency and accuracy. Previous studies have successfully employed CNN for classifying various objects, including fruits. The CNN method is implemented using the VGG16 model training approach and prepared training data. This study focuses on three types of bananas—male,